2017
DOI: 10.5376/ijms.2017.07.0040
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Fish and Otolith Size of the Blackspot Snapper <i>Lutjanus ehrenbergii</i> (Peters, 1869) Collected from the Coast of Muscat City, Sea of Oman

Abstract: In studies of prey-predator relationships, population dynamics and ichthyo-archaeology, the fish otoliths are commonly used to decide taxon, age and size of the teleost fishes. They can also be used to calculate the size of the prey. The relationships between otolith measurements (length and width) and fish body proportions (head, total and standard lengths) were estimated for blackspot snapper Lutjanus ehrenbergii collected from the Oman's Sea, at Muscat City. Otolith length and width was shown to be good ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…Morphometric characteristics of the sagittal otoliths of YOY common pandora were linearly related to the logarithm of fish TL. Our results are consistent with those of other studies and indicate that the relationships between fish TL and otolith morphometric measurements are usually log linear (Ayyildiz et al, 2014;Dehghani et al, 2016;Al-Busaidi et al, 2017). However, according to Lleonart et al (2000), the linear model is not appropriate because it cannot detect changes in the shape of otoliths.…”
Section: Discussionsupporting
confidence: 90%
“…Morphometric characteristics of the sagittal otoliths of YOY common pandora were linearly related to the logarithm of fish TL. Our results are consistent with those of other studies and indicate that the relationships between fish TL and otolith morphometric measurements are usually log linear (Ayyildiz et al, 2014;Dehghani et al, 2016;Al-Busaidi et al, 2017). However, according to Lleonart et al (2000), the linear model is not appropriate because it cannot detect changes in the shape of otoliths.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly Jawad (2012) and Jawad et al (2012a) in Sardinella sindensis and Sillago sihama collected from the Persian Gulf near Bandar Abbas and Jawad et al (2020) in Sarotherodon melanotheron and Coptodon guineensis examined from Lake Ahémé and Porto-Novo Lagoon, Bénin, found the same results, except that a trend of increase in the value of asymmetry with fish length has been observed in the otolith width only. However, Al-Busaidi et al (2017) reported that both the length and width measurements of the otolith estimated from L. ehrenbergii in the Sea of Oman at Muscat City are good indicators for fish length and there is symmetry between the left and right otoliths. In addition, Kontaş et al (2018) investigated the fluctuating asymmetry of the otolith area, length, perimeter and width in four groups of Merlangius merlangus collected from the Middle Black Sea and declared that the otolith area had the highest asymmetry, while the length had the lowest.…”
Section: Discussionmentioning
confidence: 99%
“…However, Al-Busaidi et al . (2017) reported that both the length and width measurements of the otolith estimated from L . ehrenbergii in the Sea of Oman at Muscat City are good indicators for fish length and there is symmetry between the left and right otoliths.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations